OP94 Evidence for the Effectiveness Ofopiate Substitution Treatment in Relation to HIV Transmission in People who Inject Drugs: A Systematic Review and Meta-Analysis. (17th September 2012) - MacArthur, GJ; Minozzi, S; Martin, N; Vickerman, P; Bruneau, J; Davoli, M; Hickman, M
Abstract : Background: Injecting drug use is a major risk factor for the acquisition and transmission of HIV among people who inject drugs (PWID), and between PWID and the wider community. Worldwide there are an estimated 15.9 million PWID of whom 3 million may be HIV-positive. Methadone and buprenorphine (opiate substitution treatments, OST) reduce heroin use, injecting risk behaviour, and drug related mortality and are included in the World Health Organization list of essential medicines. A small number of individual cohort studies and a Cochrane narrative systematic review suggest that OST may reduce HIV incidence, but no pooled quantitative synthesis has been carried out. We have undertaken a systematic review and meta-analysis of published and unpublished studies to quantify the effect of OST on HIV transmission. Methods: Medline, EMBASE and PsychINFO were searched to October 2011 to identify studies that examined the effectiveness of OST in relation to HIV transmission. Authors of prospective studies that assessed HIV incidence in PWID were contacted to obtain unpublished data. Results: Fifteen studies conducted in seven countries were relevant for inclusion. Data from ten of the studies were pooled, two of which were unpublished. Analysis included over 22, 000 person-years of follow-up and 738 incident HIV infections. Preliminary random effects meta-analysis demonstrates that OST reduces risk of HIV transmission among PWID by 49% (RR 0.51, 95% CI 0.37–0.71; p<0.001) although there was significant heterogeneity between studies (I 2 59.5%, χ 2 22.2, p=0.008). Study-level covariates including publication year, gender, median age, and ethnicity of participants did not significantly influence the impact of OST in meta-regression analyses. However, sub-group analysis demonstrated that whilst continuous OST significantly reduced risk of HIV infection, the effectiveness of interrupted or detoxification treatment was less clear (RR 1.26, 95% CI 0.77–2.07; p=0.360). Conclusion: These preliminary data provide further evidence that OST can reduce the risk of HIV infection among PWID and for the first time quantify the effect. Ensuring sufficient coverage of OST as part of a package of harm reduction interventions is critical to reduce the burden of HIV among PWID and to prevent onward transmission between PWID and to the wider community.